HISTORY AND CONTEXTUALIZATION IN ESTEREOCHEMICAL EDUCATION: A PROPOSED APPROACH TO HIGH SCHOOL (Revista Contexto & Educação, 2020)
The challenges of teaching stereochemistry have been studied for decades. Problem solving at the three-dimensional level is considered as one of the sources of difficulty. In addition, lacking motivation for learning is a barrier to teaching chemistry. Searching for a teaching strategy and having as input the Theory of Conceptual Fields, which presupposes that a concept becomes significant for the subject from a variety of situations, an exploratory case study was carried out with students of Technical High School in Chemistry. The study reported is a cut from a doctoral research, and exclusively addresses the impact on the level of understanding of the area through the use of a didactic unit using a focus on historical and contextual issues. Using the mixed method and content analysis, it was verified through pre and post tests that the use of didactic unit allowed students to comprehend a variety of situations, increasing their repertoire of knowledge, which makes the concept meaningful and collaborates for the motivation in the classroom. This meaning and motivation can contribute to the field of stereochemistry and to overcome the unique difficulties of the area.
Keywords: History of science. Stereochemistry. Contextualization. Conceptual Field Theory.